Legal entanglements : law, rights and the battle for legitimacy in divided Germany, 1945-1989 - Gehrig, Sebastian (Berghahn, 2021)
"Of all the dramatic ruptures occasioned by the division of East and West Germany, one of the most consequential was in the realm of law, as two nations scrambled to put the Nazi past behind them and forge new legal regimes. Legal Entanglements gives a comprehensive account of this often-overlooked chapter in postwar history, showing how the GDR and FRG established mutually incompatible legal frameworks that premised each state as the sole legitimate successor to the German Reich. Drawing on wide-ranging archival research and recently declassified documents, it follows the politicians, intellectuals, and other historical actors who helped their nations to navigate volatile legal circumstances"--